(untitled) (Perner’s Contacts, 2018)
During processing of crude oil are producing many products, which are process in refinery or products are transported some type of transport to consignee. Transportation of crude products are realized by pipeline, road, barge and railway freight transport. Advantages railway are transportation of large quantity in a short time and long distances for low costs.